Perinatal Exposure to Glufosinate Ammonium Herbicide Impairs Neurogenesis and Neuroblast Migration through Cytoskeleton Destabilization - Herzine, Ameziane; Laugeray, Anthony; Feat, Justyne; Menuet, Arnaud; Quesniaux, Valérie; Richard, Olivier; Pichon, Jacques; Montécot-Dubourg, Céline; Perche, Olivier; Mortaud, Stéphane (Frontiers in Cellular Neuroscience, 2016)
Neurogenesis, a process of generating functional neurons from neural precursors, occurs throughout life in restricted brain regions such as the subventricular zone (SVZ). During this process, newly generated neurons migrate along the rostral migratory stream to the olfactory bulb to replace granule cells and periglomerular neurons. This neuronal migration is pivotal not only for neuronal plasticity but also for adapted olfactory based behaviors. Perturbation of this highly controlled system by exogenous chemicals has been associated with neurodevelopmental disorders. We reported recently that perinatal exposure to low dose herbicide glufosinate ammonium (GLA), leads to long lasting behavioral defects reminiscent of Autism Spectrum Disorder-like phenotype in the offspring (Laugeray, Herzine et al. 2014) . Herein, we demonstrate that perinatal exposure to low dose GLA induces alterations in neuroblast proliferation within the SVZ and abnormal migration from the SVZ to the olfactory bulbs. These disturbances are not only concomitant to changes in cell morphology, proliferation and apoptosis, but are also associated with transcriptomic changes. Therefore, we demonstrate for the first time that perinatal exposure to low dose GLA alters SVZ neurogenesis. Jointly with our previous work, the present results provide new evidence on the link between molecular and cellular consequences of early life exposure to the herbicide GLA and the onset of ASD-like phenotype later in life.